Klasterisasi Kasus Kekerasan Terhadap Anak dan Perempuan Berdasarkan Algoritma K-Means - adawiyah, noviya; Sulistiyowati, Nina; Jajuli, Mohamad (Generation Journal, 2021)
Violence is action or threats against themselves alone, a group of people or community a group of people or community, loss psychologist, trauma, or deprivation of rights. District Karawang is on of the district that exist in the province of Jawa Barat. Violence that befell children and women in the area of Karawang bloom occurs, such as the lacj awareness of the victim to follow up cases that happened. The purpose of knowing the results of the cluster of cases of violence against children and women into three clusters are statterd in every sub-district in the District Karawang with category level of hardness low, medium or high in order that the government Karawang can provide treatment that is defferent and more targeted and focused on the results ot the analysis for each-each district. Data mining is the process of extracting data to obtain new information. In this study using CRIPS-DM methodology.Research is doing computation algorithm k-means clustering on the data of case of violence against children and women in 2016-2020. Results of testing using tools WEKA 3.8 earnded three cluster or the three categories of the level of violence that is cluster 0 there are 4 members who categorized the level of violence high, cluster 1 there are 2 members categorized the level of violence medium, and cluster 2 there are 24 members who categorized the level of violence low, the results of clustering is evaluated using equation testing purity measure, generate value purity 0,617, case that shows the cluster is quite good.